Aging and cancer: The role of macrophages and neutrophils - Jackaman, Connie; Tomay, Federica; Duong, Lelinh; Abdol Razak, Norbaini Bintu; Pixley, F.; Metharom, Pat; Nelson, Delia (2017)
Impaired immune function has been implicated in the declining health and higher incidence of cancer in the elderly. However, age-related changes to immunity are not completely understood. Neutrophils and macrophages represent the first line of defence yet their ability to phagocytose pathogens decrease with aging. Cytotoxic T lymphocytes are critical in eliminating tumors, but T cell function is also compromised with aging. T cell responses can be regulated by macrophages and may depend on the functional phenotype macrophages adopt in response to microenvironmental signals. This can range from pro-inflammatory, anti-tumorigenic M1 to anti-inflammatory, pro-tumorigenic M2 macrophages. Macrophages in healthy elderly adipose and hepatic tissue exhibit a more pro-inflammatory M1 phenotype compared to young hosts whilst immunosuppressive M2 macrophages increase in elderly lymphoid tissues, lung and muscle. These M2-like macrophages demonstrate altered responses to stimuli. Recent studies suggest that neutrophils also regulate T cell function and, like macrophages, neutrophil function is modulated with aging. It is possible that age-modified tissue-specific macrophages and neutrophils contribute to chronic low-grade inflammation that is associated with dysregulated macrophage-mediated immunosuppression, which together are responsible for development of multiple pathologies, including cancer. This review discusses recent advances in macrophage and neutrophil biology in healthy aging and cancer.